2019
DOI: 10.1016/j.ajpath.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Specialized Proresolving Mediator Profiles in a Novel Experimental Model of Lymphatic Obstruction and Intestinal Inflammation in African Green Monkeys

Abstract: Changes in the intestinal lymphatic vascular system, such as lymphatic obstruction, are characteristic features of inflammatory bowel diseases. The lymphatic vasculature forms a conduit to enable resolution of inflammation; this process is driven by specialized endogenous proresolving mediators (SPMs). To evaluate contributions of lymphatic obstruction to intestinal inflammation and to study profiles of SPMs, we generated a novel animal model of lymphatic obstruction using African green monkeys. Follow-up stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…The first finding in our study was a decrease in biodiversity in the AGM microbiome 7-dyas after induction of the ATLAS model. This timepoint also represents the peak of the inflammatory state [14]. In support of this, Ott et al [33], reported that the diversity of the gut flora in CD was reduced to 50% of that seen in controls and was even further reduced (30%) in UC.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The first finding in our study was a decrease in biodiversity in the AGM microbiome 7-dyas after induction of the ATLAS model. This timepoint also represents the peak of the inflammatory state [14]. In support of this, Ott et al [33], reported that the diversity of the gut flora in CD was reduced to 50% of that seen in controls and was even further reduced (30%) in UC.…”
Section: Discussionmentioning
confidence: 74%
“…An in-depth description of the ATLAS model, along with the physiological and inflammatory data used to define the model was reported in a previous paper [14]. Briefly, animals underwent a laparotomy and intestinal and mesenteric lymphatic vessels of the distal ileum and ascending colon were identified by subserosal injections of Isosulfan blue (300 l, 1%, Lymphazurin TM , Covidien, New Haven, CT, USA).…”
Section: The Atlas Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Crohn’s disease can be modelled by surgically obstructing the lymphatics in the African green monkey. This model was used to measure levels of SPMs in the gastrointestinal tract in response to injury ( Table 2 ) [ 110 ]. The peak of the inflammatory response, recorded 7 days post lymphatic obstruction, was characterized by the increase in inflammatory cytokines and chemokines.…”
Section: Specialized Pro-resolving Mediators and The Lymphatic Sysmentioning
confidence: 99%
“…In an extension of these studies, we conducted the present in vivo study to evaluate potential anti-diabetic action of anti-inflammatory metabolite of DHA, resolvin D1. Resolvin D1 (RVD1) reduces inflammation and showed promise in chronic inflammatory diseases, such as rheumatoid arthritis, inflammatory bowel disease, and asthma [ 19 , 20 , 21 , 22 , 23 , 24 ]. However, its role in the prevention of T1DM has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%